Ecological Mythology of the Tegalwaru Community: An Actantial and Functional Analysis of the Kampung Hilang Legend - Ahmad Abdul Karim; Djoko Saryono; Karkono Karkono (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
Tegalwaru community in Karawang Regency, West Java, is closely tied to agrarian traditions and ecological values that are expressed through local myths. Among these, the Kampung Hilang (Vanished Village) legend is particularly significant, recounting the collapse of a once harmonious life in Bakan Jati Village due to the community’s Functional disrespect toward a sacred being. structure of the legend as a legend representation of ecological mythology in Tegalwaru society. A qualitative approach was employed, with data obtained through interviews, observations, and documentation in Mekarbuana Village. To ensure credibility and validity, triangulation of sources, methods, and time was implemented. The analysis identified six actantial roles: sender (nature and Dewi Sri), subject (Bakan Jati residents), object (ecological harmony), helper (local traditions, rituals, and natural fertility), opponent (greed, moral violations, and loss of empathy), and receiver (Bakan Jati residents). Functionally, the narrative develops through three stages: an initial state of harmony; a transformation marked by trials, conflicts, and ecological disasters; and an ending in which Bakan Jati Village vanishes as a consequence of ecological transgression. The findings highlight the vital role of local mythology in shaping ecological consciousness and suggest its integration into culturally grounded environmental education.